Impact of QRS duration on left ventricular remodelling and survival in patients with heart failure. Issue 11 (November 2021) - Straw, Sam; McGinlay, Melanie; Gierula, John; Lowry, Judith E.; Paton, Maria F.; Cole, Charlotte; Drozd, Michael; Koshy, Aaron O.; Mullens, Wilfried; Cubbon, Richard M.; Kearney, Mark T.; Witte, Klaus K.
Abstract : Aims: In patients with chronic heart failure, QRS duration is a consistent predictor of poor outcomes. It has been suggested that for indicated patients, cardiac resynchronization therapy (CRT) could come sooner in the treatment algorithm, perhaps in parallel with the attainment of optimal guideline-directed medical therapy (GDMT). We aimed to investigate differences in left ventricular (LV) remodelling in those with narrow QRS (NQRS) compared with wide QRS (WQRS) in the absence of CRT, whether an early CRT strategy resulted in unnecessary implants and the effect of early CRT on outcomes. Methods: Our cohort consisted of 214 consecutive patients with LV ejection fraction (LVEF) of 35% or less who underwent repeat echocardiography 1 year after enrolment. Of these, 116 patients had NQRS, and 98 had WQRS of whom 40 received CRT within 1 year and 58 did not. Results: In the absence of CRT, patients with WQRS had less LV reverse remodelling compared with those with NQRS, with differences in ΔLVEF (+2 vs. +9%, P < 0.001) ΔLV end-diastolic diameter (−1 vs. −2 mm, P = 0.095), ΔLV end-systolic diameter (−2 vs. −4.5 mm, P = 0.038), LV end-systolic volume (−12.6 vs. −25.0 ml, P = 0.054) and LV end-diastolic volume (−7.3 vs. −12.2 ml, P = 0.071). LVEF was more likely to improve by at least 10% if patients had NQRS or received CRT ( P = 0.08). Thirteen (24%) patients with WQRS achieved an LVEF greater than 35% in the absence of CRT; however, none achieved greater than 50%. Conclusion: A strictly linear approach to heart failure therapy might lead to delays to optimal treatment in those patients with the most to gain from CRT and the least to gain from GDMT. Abstract : Supplemental Digital Content is available in the text